Employees’ perceptions towards moderating effect of safety climate on the relationship between safety management practices and safety performance of SMEs industry in Kelantan. - Nik Nor Hidayah Ismail (2020)
Safety management practices have been aggressively put into action to encourage employees’ involvement and commitment towards safety related matters but yet there are still many incidents and accidents reported involving small and medium enterprises industry. However, the study involving employees’ perceptions towards safety management practices and safety performance are still lacking particularly in small and medium enterprises. Therefore, this study measures on the employees’ perceptions towards moderating effect of safety climate on the relationship between safety management practices namely management commitment to safety, employee involvement to safety, safety management system, safety culture, and safety training towards better safety performance. Safety management practices improve working conditions; positively influence employees’ attitudes and behaviours with regard to safety, thereby reducing accidents in workplace. This study uses questionnaires as its instrument. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). A total of 350 questionnaires were sent to the identified Small Medium Enterprise in Kelantan, with response rate of 300 questionnaires (85.71%). The study found that all dimensions of safety management practices have a positive relationship with the safety performance. While for moderating effect of safety climate on the relationship between safety management practices and safety performance, only safety management system has positive relationship using post-hoc test. These findings provide valuable guidance for researchers in identifying the mechanisms by which they can improve safety at workplace.